Bioenergetics and energy systems in sport performance: A narrative review - Ghosh, Poulami; Ghosh, Arnab; Mukhopadhyay, Kishore (Advances in Health and Exercise, 2026)
Background: Activity is the basis of life and this quality is already present in our DNA. Performing any forms of activities or exercises energy is required. The chemical energy is stored and regenerate in the form of ATP. The three energy systems of our body that is responsible for the liberation of energy depending upon the volume and intensity of work namely ATP PC, oxidative, and glycolytic which is again dependent upon three major types of muscle fiber. The dominance of these systems varies across different sporting events. Therefore, understanding bioenergetics helps in selecting the most suitable sport based on an individual’s physiological capacity. Objective: The objective is to understand the role of bioenergetics and different energy systems (ATP-PC, anaerobic, and aerobic) in determining the energy demands of various sporting events. It also aims to relate an athlete’s physiological capacity to appropriate sports selection, thereby improving performance and guiding talent identification. Content Summary: Understanding bioenergetics helps in the scientific selection of sporting events, talent identification, and training specialization. It enhances performance, delays fatigue, and reduces the risk of injury by ensuring that athletes participate in sports best suited to their energy system efficiency. A review-based study was conducted to draw the inference of the study. Practical Implications: Bioenergetics helps in selecting suitable sporting events by matching an athlete’s dominant energy system with the specific demands of the sport. It also guides training, recovery, and nutrition strategies to improve performance and reduce fatigue and injury risk. Conclusion: All types of muscle fiber are present in the human body but their quantity is largely dependent upon the genetic endowment of an individual and partly adaptation of sports training. The present article discussed scientifically the various aspects of bioenergetics and the method of training for the development of particular muscle fiber in relation to sporting action.